2022
DOI: 10.12669/pjms.38.4.5052
|View full text |Cite
|
Sign up to set email alerts
|

Burnout prevalence and associated factors in medical students in integrated modular curriculum: A cross-sectional study

Abstract: Objectives: The present study aimed to explore the prevalence of burnout syndrome and to find the association of burnout symptoms with sociodemographic factors in medical students. Methods: A cross-sectional study was conducted between September 2019 to January 2021 at Shifa College of Medicine, Islamabad. A total of 284 medical students from the first year to the fifth year participated in this cross-sectional study. After taking informed consent, students were asked to record responses on the Burnout C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Sufficient sleep has lately been emphasized as a public health primacy in the Healthy People 2020 initiative, with both inadequate and prolonged sleep linked to increased probability of depression and poor health. 10 , 11 A sleep span of < 7 hours is associated with an increased hazard of cardiovascular and cerebrovascular diseases, malignant neoplasms, accidents, septicemia and metabolic disorders. 12 The quality and extent of sleep is also affected by workplace environment and job demands, with various studies linking workplace stresses to sleep disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Sufficient sleep has lately been emphasized as a public health primacy in the Healthy People 2020 initiative, with both inadequate and prolonged sleep linked to increased probability of depression and poor health. 10 , 11 A sleep span of < 7 hours is associated with an increased hazard of cardiovascular and cerebrovascular diseases, malignant neoplasms, accidents, septicemia and metabolic disorders. 12 The quality and extent of sleep is also affected by workplace environment and job demands, with various studies linking workplace stresses to sleep disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Former smokers were defined as individuals who had smoked over 100 cigarettes in their lifetime but were not currently smoking at the time of the interview. Participants who did not meet both criteria were classified as non-smokers [26]. Participants with an alcohol consumption of 20 g or more per day were categorized as heavy drinkers [49].…”
Section: Measurementsmentioning
confidence: 99%
“…Anxiety disorders are biopsychosocial conditions distinguished by disproportionate and enduring fear of everyday occurrences alongside behavioral and somatic symptoms [26]. Anxiety disorders are the most common psychiatric disorders worldwide [27], with lifetime prevalence rates ranging from 14.5% to 33.7%, according to a large prevalence study conducted in the United States [28].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the possibility that a hybrid scheme for MILPs can modify the stress level, the following hypotheses are proposed for this study: Income Some studies on burnout have established that income and financial strain are variables that affect burnout (Irshad et al, 2022;Soares et al, 2007), and other have shown a positive correlation between financial stress and burnout (Kloutsiniotis et al, 2022). It is thus logical to expect working mothers with low incomes and high family demands to be affected by their level of burnout.…”
Section: Hybrid Working Schemesmentioning
confidence: 99%